Byzantium/modernism
1 online resource (xxiv, 369 pages)
Keywords: Byzantium/Modernism features contributions by fourteen international scholars and brings together a diverse range of interdisciplinary essays on art, architecture, theatre, film, literature, and philosophy, which examine how and why Byzantine art and image theory can contribute to our understanding of modern and contemporary visual culture. Particular attention is given to intercultural dialogues between the former dominions of the Byzantine Empire, with a special focus on Greece, Turkey, and Russia, and the artistic production of Western Europe and America. Together, these essays invite the reader to think critically and theoretically about the dialogic interchange between Byzantium and modernism and to consider this cross-temporal encounter as an ongoing and historically deep narrative, rather than an ephemeral or localized trend. Contributors are Tulay Atak, Charles Barber, Elena Boeck, Anthony Cutler, Rico Franses, Dimitra Kotoula, Marie-José Mondzain, Myroslava M. Mudrak, Robert S. Nelson, Robert Ousterhout, Stratis Papaioannou, Glenn Peers, Jane A. Sharp and Devin Singh.